Advancing Energy-Efficient Drying: Integration of Phase Change Material (PCM) and Heat Pipe for Temperature Control in Dryers - Irvan Ari Ramadhan; Nasruddin A. Abdullah; Nazaruddin Abdul Rachman; Fazri Amir (Fakultas Teknik Universitas Samudra, 2023)
The existing drying system struggles with efficiency and costs, contradicting its intended resource-saving purpose. Addressing these issues could generate increased interest in its utilization. To tackle this, precise control of the dryer's temperature and optimization of the heat source are essential for obtaining accurate and real-time data. Employing a quantitative approach, the researcher conducted a case study, performing tests subsequent to the completion of the dryer's assembly. These tests encompassed temperature measurements on both the core and periphery of the paraffin medium, as well as at the lower, middle, and upper sections of the heat pipes. Diverse voltage levels (150V, 180V, 200V, 220V) and two distinct airflow velocities (1 m/s and 2 m/s) were implemented. The study yielded a noteworthy finding: at 200 volts and a 2m/s airflow, a stable temperature of 94.8 ºC was maintained for an impressive duration of 1 hour and 5 minutes during testing. This promising outcome holds significant implications for enhancing the system's efficiency.